The TT genotype of the MTHFR 677C > T polymorphism increases susceptibility to premature coronary artery disease in interaction with some of the traditional risk factors - Sarecka-Hujar, Beata; Zak, Iwona; Krauze, Jolanta (Acta medica (Hradec Kralove), 2012)
BACKGROUND: The presence of several risk factors (genetic and non-genetic) has greater impact on the risk of premature coronary artery disease (CAD) than single risk factor. OBJECTIVE: The aim of the study was to establish possible relations between genotypes and alleles of 677C>T polymorphism of MTHFR gene and some traditional risk factors e.g. elevated levels of lipid parameters and smoking in development of premature CAD. METHODS: The groups comprised 152 patients with angiographically documented premature CAD (aged 42.9 +/- 5.5) and 121 age-matched blood donors (aged 42.3 +/- 6.5) were studied. The MTHFR 677C>T polymorphism was genotyped with Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method. RESULTS: Patients with TT genotype who simultaneously smoked had increased risk of premature CAD compared to non-smoking cases with CC genotype (OR = 24.62). We also found that individuals with TT genotype and elevated LDL-cholesterol (LDL-chol.) level had significantly higher risk of CAD (OR = 9.92) than individuals with normal LDL-chol. level and CC genotype. CONCLUSIONS: The present study shows that simultaneous presence of MTHFR TT genotype and smoking or elevated levels of LDL-chol. influences the risk of premature CAD. This findings give interesting contribution to gene-environment interaction problem that may have clinical implications in the future.
Keywords: lipidy; Male; Smoking; kouření; genotyp; Methylenetetrahydrofolate Reductase (NADPH2); nemoci koronárních tepen; Humans; rizikové faktory; mužské pohlaví; Female; Coronary Artery Disease; polymorfismus genetický; ženské pohlaví; Genetic Predisposition to Disease; Polymorphism, Genetic; Lipids; Adult; methylentetrahydrofolátreduktasa (NADPH2); genetická predispozice k nemoci; dospělí; lidé; Genotype; Risk Factors